Relating MRI changes to motor deficit after ischemic stroke by segmentation of functional motor pathways. - Pineiro, R; Pendlebury, S; Smith, S; Flitney, D; Blamire, A; Styles, P; Matthews, P (2000)
BACKGROUND AND PURPOSE: Infarct size on T2-weighted MRI correlates only modestly with outcome, particularly for small strokes. This may be largely because of differences in the locations of infarcts and consequently in the functional pathways that are damaged. To test this hypothesis quantitatively, we developed a "mask" of the corticospinal pathway to determine whether the extent of stroke intersection with the pathway would be more closely related to clinical motor deficit and axonal injury in the descending motor pathways than total stroke lesion volume. METHODS: Eighteen patients were studied > or =1 month after first ischemic stroke that caused a motor deficit by use of brain T2-weighted imaging, MR spectroscopic (MRS) measurements of the neuronal marker compound N-acetyl aspartate in the posterior limb of the internal capsule, and motor impairment and disability measures. A corticospinal mask based on neuroanatomic landmarks was generated from a subset of the MRI data. The maximum proportion of the cross-sectional area of this mask occupied by stroke was determined for each patient after all brain images were transformed into a common stereotaxic brain space. RESULTS: There was a significant linear relationship between the maximum proportional cross-sectional area of the corticospinal mask occupied by stroke and motor deficit (r(2)=0.82, P<0.001), whereas the relationship between the total stroke volume and motor deficit was better described by a cubic curve (r(2)=0.76, P<0.001). Inspection of the data plots showed that the total stroke volume discriminated poorly between smaller strokes with regard to the extent of associated motor deficit, whereas the maximum proportion of the mask cross-sectional area occupied by stroke appeared to be a more discriminatory marker of motor deficit and also N-acetyl aspartate reduction. CONCLUSIONS: Segmentation of functional motor pathways on MRI allows estimation of the extent of damage specifically to that pathway by the stroke lesion. The extent of stroke intersection with the motor pathways was more linearly related to the magnitude of motor deficit than total lesion volume and appeared to be a better discriminator between small strokes with regard to motor deficit. This emphasizes the importance of the anatomic relationship of the infarct to local structures in determining functional impairment. Prospective studies are necessary to assess whether this approach would allow improved early estimation of prognosis after stroke.